LOCAÇÃO DE POÇOS TUBULARES PROFUNDOS COM VLF NO ESTADO DO CEARÁ - LEITE, CARLOS EDUARDO SOBREIRA; CORDEIRO, WALBER; SALES NETO, PORFÍRIO; GOMES, LUCIANO ÁLVARO MAIA (Águas Subterrâneas, 1994)
RESUMO NÃO DISPONÍVEL